A RANDOMISED, COMPARATIVE STUDY OF GRID LASER AND SUBTHRESHOLD MICROPULSE DIODE LASER IN THE TREATMENT OF DIFFUSE DIABETIC MACULOPATHY - Chellakumar, Vikram; ., Rajarathnam; Vijai, Cornelius (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Diabetic retinopathy is a major cause of visual impairment in both developing and developed countries. The two important complications are macular edema and proliferative diabetic retinopathy. Laser treatment can reduce vision loss in both proliferative diabetic retinopathy and diabetic macular edema. Early treatment of diabetic retinopathy study shows that immediate laser treatment reduces the risk of moderate visual loss by at least 50%. Thermal tissue damage is the main cause of many potential complications of conventional photocoagulation that may lead to immediate and late visual loss. A subthreshold diode micropulse (SDM) laser targets retinal pigment epithelium (RPE); it is maximally absorbed by the melanosomes of the RPE and underlying choroid while sparing the neurosensory retina. SDM laser minimizes chorioretinal damage as there is no thermal effect or injury despite achieving photocoagulation effects. To compare, the effectiveness of SDM laser versus grid laser photocoagulation for the treatment of clinically significant macular edema in diabetic patients. To study, the outcome and adverse effects of laser treatments in both modalities. Methods: All Type 2 diabetic patients presenting to the ophthalmology department outpatient department were screened for diffuse diabetic macular edema and 60 eyes were enrolled in the study. They were divided into two groups of 30 eyes each and randomly assigned to receive either conventional grid laser or SDM laser. A detailed clinical examination which included visual acuity, color vision, visual fields (central 10Â°), fundus photos, and fundus flourescein angiography were done prior to the laser treatment and at 6 weeks and 3 months follow-up. Results: Conventional grid laser caused a significant resolution of macular edema, angiographically, whereas SDM laser showed worsening at 3 months follow-up. Our study did not show an alteration of central 10Â° of visual field or color vision defects in both the groups, which suggest significant functional damage is not caused by both treatment modalities. We found in our study that conventional Grid laser was better at 3 months follow-up in improving/stabilizing visual acuity and macular edema (angiographically). A single sitting of grid laser is better than SDM laser in diffuse diabetic maculopathy. Keywords: Diabetic retinopathy, Diabetic macular edema, Grid laser, Subthreshold micropulse diode laser.